Anti-ALDOA antibody: a novel diagnostic-associated autoantibody in myasthenia gravis - Zhang, Mengdi; Zhang, Yingna; Liu, Peipei; Gao, Qingye; Liu, Qian; Zhou, Xinyue; Liu, Ruichen; Zhao, Xue; Zhang, Jing; Hu, Jia; Dong, Haiyan; Liu, Jing; et al. (Frontiers in Neurology, 2025)
This study identified novel autoantibodies in patients with seronegative myasthenia gravis (SNMG).Autoantibodies in SNMG sera were screened using a targeted binding assay (TBA). The target antigen was identified via immunoprecipitation and mass spectrometry, and validated by western blotting using a commercial antigen. A cell-based assay (CBA) employing HEK293 cells expressing the identified antigen was established to detect specific antibodies in 676 MG patients and 20 controls.Aldolase A (ALDOA) was identified as a novel autoantigen. Anti-ALDOA antibodies (ALDOA-Ab) demonstrated high diagnostic specificity in SNMG and were also detected in seropositive MG patients, with positivity rates of 4.89% in AChR-Ab’ and 2.86% in MuSK-Ab’ subgroups. ALDOA-Ab was predominantly of the IgG1 subclass. ALDOA-Ab may serve as a potential diagnostic biomarker for MG. Further studies are needed to investigate its pathogenic role.